Effect of Implicit Prejudice on Intergroup Conflict: The Cognitive Processing Bias Perspective - Sun, Lian-Rong (Journal of interpersonal violence, 2021)
Principles of intergroup conflict are a core issue in social psychology fields. Studies have found that social prejudice has a significant correlation with intergroup conflict, apart from the personal characteristics and the contextual factors. However, none of those studies concentrated on the triggering role of the prejudice to the social phenomena in Eastern culture. Accordingly, the dependent variable detection paradigms used in three experiments were the Emotional Stroop Task, the Lexical Decision Task (LDT), and the Story Completion Protocol (SCP), the present research took the patient–physician conflict in domestic China as the example to detect the effect of social prejudice on the attention selective bias, memory accessibility, and the explanation of attribution bias of the aggressive information processing during the triggering of patient–physician intergroup conflict. The result showed that there was social patient–physician prejudice dissociation, which means that implicit patient–physician prejudice was observed but explicit social prejudice was not. In addition, the implicit patient–physician prejudice priming had a significant effect on patients’ reaction times of Emotional Stroop task and SCP, but no effect of LDT. It indicated that the implicit prejudice did not improve memory accessibility in the later stages of information processing, but rather triggered selective attention bias and hostile attribution bias in preceding stages. Such a conclusion supported the Interpretation-First Model of aggressive information processing.